A Chancellor's Tale : Transforming Academic Medicine - Snyderman, Ralph (Book collections on Project MUSE., 2016)
Former Chancellor of the Duke University Medical Center Dr. Ralph Snyderman reflects on his key role in instituting a series of changes that led the medical center to be internationally known for its academic medicine, initiatives in clinical research, genetics, and neurosciences, and the development of new health care models.